Emotion regulation goals and strategies among individuals with varying levels of sensory processing sensitivity: a latent profile analysis - Liu, Yiran; Tian, Feng (Frontiers in Psychology, 2024)
Background: Emotion regulation (ER) has emerged as a significant factor influencing the well-being of individuals with high sensory processing sensitivity (SPS). However, the interaction between SPS and the underlying mechanisms of ER remains largely unexplored.Objective: This study aimed to (a) identify profiles of SPS and ER competency using latent profile analysis (LPA), and (b) investigate the ER goals and strategy use among each profile to better understand ER patterns in highly sensitive individuals with lower ER proficiency. Methods: A total of 813 Chinese college students (mean age = 21.53±2.48; 74.41% female) completed the Highly Sensitive Person Scale, 16-item Difficulties in Emotion Regulation Scale, Emotion Regulation Goals Scale, Emotion Regulation Questionnaire, and the rumination subscale from the Cognitive Emotion Regulation Questionnaire.Results: The LPA identified three profiles: "Low SPS -High ER Competency" (41%), "Moderate SPS and ER Competency" (41%), and "High SPS -Low ER Competency" (18%). ER goals varied significantly among these groups. The "High SPS -Low ER Competency" group predominantly pursued contra-hedonic and impression management goals, while the "Low SPS -High ER Competency" group focused on pro-hedonic goals. In terms of strategies, the "Low SPS -High ER Competency" group mainly used cognitive reappraisal, the "Moderate SPS -ER Competency" group leaned towards suppression, and the "High SPS -Low ER Competency" group preferred rumination and suppression.Conclusion: These findings indicate that higher SPS combined with lower ER proficiency is linked to an increased pursuit of contra-hedonic and impression management goals and a reliance on responsefocused strategies. This pattern offers new insights for developing psychological support strategies for highly sensitive individuals experiencing mental distress.